(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
The organization of fair governance occupies a priority position. The fact that the rules of governance have been raised to a new level not only in the political governance system, but also represents a sign of the competence of each leader in his profession. In general, the study of the subject of leadership, its moral qualities, and models related to the organization of fair governance is becoming increasingly relevant. That is why the issue of improving the moral and aesthetic culture of modern leadership is becoming one of the urgent problems of social philosophy